2013
DOI: 10.1177/2041386613492787
|View full text |Cite
|
Sign up to set email alerts
|

The cognitive underpinnings of adaptive team performance in ill-defined task situations

Abstract: As the nature of work changes due to technology, organizational restructuring, and globalization, complex tasks have emerged that necessitate the use of teams. Oftentimes, teams complete tasks that have more than one plausible solution or engage in performance episodes under uncertain circumstances. Therefore, teams are called upon to be highly adaptable to these ill-defined tasks by responding to continuous changes in the task environment. We propose that dimensions of team cognition (i.e., shared mental mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
55
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(57 citation statements)
references
References 67 publications
1
55
0
1
Order By: Relevance
“…Limited research is available on team learning in these contexts (Salas, Guthrie, & Burke, 2007; van der Haar et al, 2015; Zajac et al, 2014). van der Haar and colleagues (2015) showed that in EMCC teams constructive conflict makes the difference.…”
Section: Team Leader Structuring Behaviors and Constructive Conflictmentioning
confidence: 99%
“…Limited research is available on team learning in these contexts (Salas, Guthrie, & Burke, 2007; van der Haar et al, 2015; Zajac et al, 2014). van der Haar and colleagues (2015) showed that in EMCC teams constructive conflict makes the difference.…”
Section: Team Leader Structuring Behaviors and Constructive Conflictmentioning
confidence: 99%
“…This study sought to test the proposition that team learning is a crucial factor for transactive memory development (Zajac et al, 2014). Moreover, as team learning is an ongoing process over the complete life cycle of a team, comprising knowledge-and communicationbased learning behaviours to create, store, and retrieve knowledge at the team level, we assumed that in the different phase of team development differential relationships exist between these team learning behaviours and transactive memory development.…”
Section: Discussionmentioning
confidence: 99%
“…Following their line of thinking, we analyse the team phase-specific influence of communication-and knowledge-based team learning behaviours in face-to-face teams on transactive memory development, as suggested in the literature (Zajac et al, 2014). In the following, we first explain the concept of team learning before we continue with the analysis of different team learning behaviours and their influence on transactive memory formation in different phases of team development.…”
Section: Transactive Memory Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…When organisations are dealing with difficult and complex tasks, teams are the chosen approach (Salas et al, 2008). This becomes more noticeable as work changes because of technology, globalisation, and organisational restructuring (Zajac et al, 2014).…”
Section: Why Teams?mentioning
confidence: 99%